Genotype-dependent strigolactones effect on stimulation of Striga hermonthica (Del.) Benth seed germination and induced systemic resistance indicators in reducing Striga weed population - Jatto, M. I.; Juraimi, A. S.; Rafii, M. Y.; Nazli, M. H.; Yusuff, O.; Naiwa, F.; Chukwu, S. C.; Halidu, J.; Datta, D. R.; Ibrahim, A. J.; Motmainna, M. (Faculty of Agricultural Sciences, Sabaragamuwa University of Sri Lanka, 2025)
Purpose: To identify the presence of GR24 and other strigolactones in 27 maize genotypes in experiments 2 and 3 m – derived from a 7 x 7 full diallel single crossing of Striga resistant and susceptible maize genotypes including their parents and two checks varieties in experiment 1 – using an LC/MS/MS analytical procedure, as well as the level of stimulation of Striga seed germination by each genotype in a germination assay. Research Method: Four different concentrations of prepared root exudates (0, 2, 4, and 6 mg/ml) were collected from 10 seedlings each of 27 genotypes for LCMS analysis and germination assay hydroponically through freeze drying. GR24 standard was used as a positive control. Findings: The LC/MS/MS analysis revealed that only two genotypes namely SUWAN X SAMMAZ 17 and Check GWG111 produced a detectable amount of a similar compound as that of the standard GR24 (m/z 321). In the germination assay, all genotypes showed varied degrees of Striga seed germination stimulation at all applied concentrations of each genotype, with GR24 at 6 mg/ml and 4 mg/ml giving the highest Striga seed germination counts of 68.83 and 47.00 respectively, while TZSTR 190 at 2 mg/ml had the least Striga seeds germination counts of 2.00. Research Limitations: The paucity of funds to acquire different strigolactone standards and repetition of the LCMS analysis using other concentrations of the samples. Originality/Value: This research paves the way for the utilization of the freeze-drying method to concentrate exudates without degrading strigolactones.